Lo cotidiano de madres adolescentes solteras en el caserío de Choquizonguillo - Huamachuco, 2014 - Guerra Morillo, Sandra Abigail (2015)
This qualitative research with descriptive approach was held in the village of Choquizonguillo Huamachuco city. Aimed to describe and analyze comprehensively the everyday experiencing unmarried teenage mothers. The guiding question was: "What is the everyday teenage single mothers in the village of choquizonguillo - Huamachuco, 2014" ?, the research subjects were 10 teenage mothers. The analysis of speeches Three categories 1) .Participation of adolescent and family child care 2) .Afrontamiento of adolescent and family with the arrival of the child (a) changes in family life 3) .Alteraciones in family life, the findings show that everyday of unmarried teenage mothers is based on caring for your child, and your home more effort this requires time and continued dedication to their attention, highlighting at all times good family life.